Pelatihan Perencanaan dan Pengelolaan Keuangan Syariah untuk Generasi Z dalam Mewujudkan Kebebasan Keuangan - Ade Maya Saraswati; Rizqa Zidnia (Jurnal Surya Masyarakat, 2022)
The financial behavior of Gen Z nowadays will have impact to the future of Indonesia as a nation. According to data provided by BPS (2020), in the year 2030 Indonesia will face demography bonus, where the composition of population will be dominated by Gen Y (27.94%) and Gen Z (25.87%). Therefore, Gen Z must be prepared to be able to contribute to further improving Indonesia economics. The purpose of this community service activity is to provide training to Gen Z regarding Islamic financial planning and management, so that Gen Z can achieve financial freedom in the future activity. Community service was held on 30 Jun 2022 at SMK Islam Malahayati, with 75 students as participants. The method used in this training is participatory. The material is delivered through lectures, followed by the practice of financial planning and financial management, as well as discussions and questions and answers from participants. The participants were enthusiastic and listened to the material well. It could be seen from the results of the answers to the questions given through the questionnaire. Not only that, the participants also gave positive feedback on this activity.